أساليب التشبيه والمجاز في سورة البقرة": “The Rhetorical Techniques of Simile and Metaphor in Surah Al-Baqarah”DOI:https://doi.org/10.5281/zenodo.17608140 (Khairulummah, 2025)
This study examines the rhetorical techniques of simile and metaphor in Surah Al-Baqarah focusing on their artistic aesthetic and communicative dimensions within the Qur’anic discourse. Through an analytical and descriptive approach the research explores how these two rhetorical devices serve as essential tools for expressing profound spiritual meanings and moral values.The study highlights that Quranic similes and metaphors transcend linguistic ornamentation functioning instead as vehicles of divine wisdom and emotional persuasion. Each image in the Surah reflects a deliberate harmony between form and meaning revealing the Quran’s unparalleled eloquence (i‘jaz bayani). Similes in this chapter clarify abstract ideas through sensory imagery while metaphors transform invisible concepts such as faith hypocrisy and guidance into vivid tangible expressions.The analysis concludes that the rhetorical beauty of Surah Al-Baqarah lies in its ability to merge intellectual depth with artistic expression. These stylistic techniques not only enhance the aesthetic value of the Qur’anic text but also strengthen its persuasive and educational power demonstrating how divine eloquence unites the heart and the mind in the pursuit o